Bridging Faith and Knowledge: A Multi-site Study of Islamic-general Education Integration in East Kalimantan’s Multicultural Context - Hasanuddin Hasanuddin; Noorthaibah Noorthaibah; Umar Fauzan (Dinamika Ilmu, 2025)
This study investigates the integration of Islamic and general education at three State Islamic Junior High Schools (MTs Negeri) in East Kalimantan; MTs Negeri 1 Balikpapan, MTs Negeri 1 Paser, and MTs Negeri 1 Kutai Kartanegara, to analyze the forms, processes, and impacts. Employing a qualitative methodology with a multi-site case study and phenomenological approach, data were collected through outdoor-indoor class observations, interviews with 13 teachers including principals, curriculum developers, and subject teachers, as well as document analysis of teaching modules, the Adiwiyata module, and the P2RA module. The integration was manifested in three main forms; curricular integration, by linking themes of aqidah akhlak into general subjects through teaching modules; social program integration, such as Adiwiyata; and the P2RA program. This process was framed within the Merdeka Curriculum by operationalizing the paradigm of integration-interconnection of knowledge and implemented through project-based learning aligned with multiple intelligences, enabling students to internalize values cognitively, affectively, and psychomotorically through diverse activities. Evaluation was conducted comprehensively, covering cognitive aspects (tests), affective aspects (attitude observation), and psychomotor aspects (practical performance). The integration also strengthens students’ religious character through behavioral transformation, deeper appreciation of values, and the ability to internalize them in both the educational environment and daily life. The noble character was developed through strategies of habituation, reflection, role modeling, and environmental support. The integration of Islamic and general education is not merely theoretical but also could be applied as a practical model for shaping a generation that excels academically while maintaining strong religious character.